BEBAN KERJA, BURNOUT DAN REWARD SEBAGAI PREDIKTOR KEPUASAN KERJA KARYAWAN PT. TI MATSUOKA WINNER INDUSTRY KABUPATEN SEMARANG - Junita Duha; Andhi Supriyadi (LPSDI Bina Patria, 2025)
Employees who are happy with their work are usually satisfied employees, who have a positive impact on their company by increasing performance and productivity. Workload, fatigue, and compensation are some of the factors that can influence job satisfaction. This research was conducted at PT. TI Matsuoka Winner Industry in Semarang Regency. Low job satisfaction can occur because some or most employees who have not been promoted sometimes feel bored with monotonous work. The purpose of this research is to find out how workload, fatigue, and compensation impact employee job satisfaction. 76 employees of PT. TI Matsuoka Winner Industry Semarang Regency is included in the sample of this research. This research data was collected through distributing questionnaires. Data is processed through multiple regression analysis. The results of multiple regression tests show: (1) Workload influences job satisfaction negatively and significantly; burnout affects job satisfaction negatively and significantly; and payment has a positive and significant effect on job satisfaction. Recommendations given to PT. IT Matsuoka Winner Industry Semarang Regency is as follows: (1) to give companies more manpower to help complete tasks. (2) to give employees more time to relax. (3) Performance appraisal takes priority when establishing promotion policies